Androgen Insensitivity Syndrome: Clinical Phenotype and Molecular Analysis in a Single Tertiary Center Cohort - Maria Sol Touzon; Natalia Perez Garrido; Roxana Marino; Pablo Ramirez; Mariana Costanzo; Gabriela Guercio; Esperanza Berensztein; Marco A. Rivarola; Alicia Belgorosky (Galenos Yayincilik, 2019)
Objective:The aim of this study was the molecular characterization of the AR gene as the cause of 46,XY disorder in our population.Methods:We studied 41, non related, 46,XY disorder of sexual differentiation index cases, having characteristics consistent with androgen insensivity syndrome (AIS). Genomic DNA was isolated from peripheral blood leukocytes of all patients and 25 family members from 17 non-related families.Results:The AR gene analysis revealed an abnormal sequence in 58.5% of the index patients. All of the complete AIS (CAIS) cases were genetically confirmed, while in the partial form (PAIS) a mutation in AR was detected in only 13 (43.3%). Molecular studies revealed other affected or carrier relatives in 87% of the index cases. The AR mutations were found spread along the whole coding sequence, with a higher prevalence in the ligand binding domain. Nine out of 23 (39%) AR mutations were novel. In 17% of patients with detected AR mutations, somatic mosaicism was detected in leucocyte DNA. In our cohort, long-term follow up gender dysphoria, raised as male or female, was not found. Finally, in suspected PAIS, the identification of AR mutation occurred significantly less than in CAIS patients.Conclusion:Improved knowledge of the components of the AR complex and signaling network might contribute to long term outcome and genetic counseling in AIS patients.